Dari Pengasingan ke Stabilitas: Menganalisis Kontribusi Politik dan Keagamaan Zerubabel dan Yosua. - Laoly, Nepho Gerson (LOGON ZOES: Jurnal Teologi, Sosial dan Budaya, 2024)
This study explores the political and religious leadership of Zerubabel and Joshua in post-exilic Judah, focusing on their collaborative efforts to rebuild the Temple and restore national identity. Zerubabel, appointed as governor by the Persian Empire, played a critical role in navigating between Persian authority and local needs, ensuring stability through administrative strategies. Meanwhile, Joshua, as High Priest, re-established religious practices and reinforced spiritual commitments. Their integrated leadership reflects the importance of combining political and religious authority to foster social and spiritual restoration. Additionally, the theological relevance of their actions aligns with covenant renewal and messianic hopes within the Jewish community, highlighting the synergy between governance and faith in achieving long-term stability in the face of external challenges.Penelitian ini mengeksplorasi kepemimpinan politik dan agama Zerubabel dan Yosua di Yehuda pasca-pembuangan, dengan fokus pada upaya kolaboratif mereka untuk membangun kembali Bait Suci dan memulihkan identitas nasional. Zerubabel, yang ditunjuk sebagai gubernur oleh Kekaisaran Persia, memainkan peran penting dalam menyelaraskan antara otoritas Persia dan kebutuhan lokal, memastikan stabilitas melalui strategi administratif. Sementara itu, Yosua, sebagai Imam Besar, membangun kembali praktik-praktik keagamaan dan memperkuat komitmen spiritual. Kepemimpinan mereka yang terintegrasi mencerminkan pentingnya menggabungkan otoritas politik dan agama untuk mendorong pemulihan sosial dan spiritual. Selain itu, relevansi teologis dari tindakan mereka selaras dengan pembaruan perjanjian dan harapan mesianis dalam komunitas Yahudi, yang menyoroti sinergi antara pemerintahan dan iman dalam mencapai stabilitas jangka panjang dalam menghadapi tantangan eksternal.